2013
DOI: 10.1111/echo.12501
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Human Atrial Natriuretic Peptide and Reduced Transthoracic Left Atrial Appendage Wall‐Motion Velocity Are Noninvasive Surrogate Markers for Assessing Thrombogenesis in Patients with Paroxysmal Atrial Fibrillation

Abstract: Higher plasma HANP and lower LAA wall-motion velocity may be noninvasive surrogate markers for assessing left atrial thrombogenesis during sinus rhythm in paroxysmal AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, the values are affected by the age, and other factors, as well Despite the fact that LA appendage could be analyzed by modern transthoracic echocardiographic methodologies including TDI, 3DSTE etc., LA appendage and pulmonary veins were excluded from evaluations. There are several aspects of HCM including genetic background, history of embolism, development of arrhythmias, etc., their relationship with the LA dysfunction was not examined in this study. The effects of dynamic obstructions on LA functional parameters were not examined in this study. LA function deteriorated in patients with sick sinus syndrome and in those with paroxysmal atrial fibrillation . However, all of our patients and controls were in sinus rhythm. This was a single‐center experience and limited by a relatively small number of HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the values are affected by the age, and other factors, as well Despite the fact that LA appendage could be analyzed by modern transthoracic echocardiographic methodologies including TDI, 3DSTE etc., LA appendage and pulmonary veins were excluded from evaluations. There are several aspects of HCM including genetic background, history of embolism, development of arrhythmias, etc., their relationship with the LA dysfunction was not examined in this study. The effects of dynamic obstructions on LA functional parameters were not examined in this study. LA function deteriorated in patients with sick sinus syndrome and in those with paroxysmal atrial fibrillation . However, all of our patients and controls were in sinus rhythm. This was a single‐center experience and limited by a relatively small number of HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Robust studies have demonstrated a relationship between ANP and the development of AF (12)(13)(14)(15). A frameshift mutation in the ANP gene was identified in patients with familial AF, and its frameshift product was shown to exhibit modified proteolytic degradation and a markedly longer half-life than ANP (14,15,31), indicating that abnormalities in ANP are involved in the pathogenesis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that overexpression of musclin can suppress the worsening of chronic heart failure (CHF) after myocardial infarction (MI) by inhibiting clearance of NP family members. A series of studies have reported the relationship of ANP or BNP with AF (12)(13)(14)(15), and NP has been recommended as a tool for the routine evaluation of patients with AF (16). Accordingly, physical exercise can up-regulate circulating musclin (17) and reduce the risk of atrial arrhythmias (18).…”
Section: Introductionmentioning
confidence: 99%
“…Since the LAA is a common site of thrombus formation, the association of the NLR with the LAA function and size has the potential to be an exciting finding. The LAA function ranges from normal to low in PAF patients ( 27 ). In the present study, the NLR also ranged from normal to high and was associated with the LAA wall motion velocity in the non-valvular PAF patients with SEC.…”
Section: Discussionmentioning
confidence: 99%